(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate the good manufacturing practices of canteens in elementary schools and day care centers in the municipality of Madalena – CE. The research was carried out in five canteens, three of which for elementary school and two day care centers, corresponding to 100% of public institutions in the city. A checklist of good manufacturing practices based on RDC nº 216/2004 of the National Health Surveillance Agency, with 182 items, was applied in school feeding units. The check list evaluated the building items, facilities and utensils; cleaning of facilities, equipment, furniture and utensils; integrated vector and urban pest control; water supply; food preparation and display, and documentation and registration. The method of evaluating the results was given by the classification into five groups, being these, "very good", "good", "fair", "poor" "very bad", corresponding respectively 91 to 100%, 70 to 90%, 50 to 69%, 20 to 49% and 0 to 19% adequacy of requirements. Microbiological analyzes were also carried out on the water used in the preparation of meals. The results showed that the percentages of adaptations in relation to good practices through the checklist ranged from 7.7 to 76.5% for the evaluated requirements. The water samples analyzed showed total coliform contamination for all analyzed samples. It is concluded that several aspects related to good manufacturing practices need to be reassessed, requiring an intervention for the adoption of pertinent actions, aiming at paying due attention to the preparation of the food provided in these units.